支援された医学的および関連したライフスタイルの意思決定 (2016)
位置に基づく被験者の生理的履歴を作成するための方法、システム、機器、およびコンピュータ可読媒体が提供される。方法は、プロセッサの支援により、位置に基づく前記被験者の生理的履歴を、前記被験者の地理位置情報データを生理的データおよび外因性データと関連付けることにより作成することを含み得る。前記地理位置情報データは、前記被験者上または前記被験者に付随する地理位置情報システムの支援により取得され得る。前記外因性データは、前記被験者の地理的位置の環境的な状態であるか、またはそれに関係するものであり得る。 Methods, systems, devices, and computer-readable media for generating a location-based physiological history of a subject are provided. Methods may include generating, with the aid of a processor, a location-based physiological history of the subject by correlating geolocation data of the subject with physiological data and exogenous data. The geolocation data may be obtained with the aid of a geolocation system on or associated with the subject. The exogenous data may be of or related to environmental conditions at a geographic location of the subject.